Zakat on Legal Entities: Towards Concept Perfection and its Regulations in Indonesia - Bafadhal, Husin (Al-Risalah, 2021)
This paper discusses zakat on legal entities and provides evidence why it requires perfection in concept and regulations if applied in Indonesia. Although it has not been discussed by previous scholars, the majority of contemporary scholars oblige legal entities to pay zakat. However, how it becomes mandatory, what criteria must be met, what are the nisab, the á¸¥awl, the mandatory percentage, and the requirements have not received significant attention from previous researchers. To make matters worse, regulations for zakat on legal entities in Indonesia are still unclear and strict, particularly concerning sanctions and methods of zakat calculation, making this paper crucial on the issue. Focusing on zakat on legal entities, this paper will highlight the development of the mukallaf meaning, criteria for legal entities that are obliged to pay zakat, provisions of the nisab, á¸¥awl, the obligatory percentage, and all the requirements. After examining relevant literature, this paper demonstrates that assets owned by a legal entity are required for zakat if they have met the general provisions and requirements stipulated in Islamic law (fiqh). As for the nisab provisions, the compulsory percentage and the zakat á¸¥awl is equal to zakat on trade, which is 85 grams of gold or 600 grams of silver, while the obligatory percentage of zakat is two and a half percent (2.5% or 1/40) and á¸¥awl is mandatory at the end of the year. This paper suggests that it is necessary to improve the concept and regulations of zakat on legal entities in Indonesia by combining fiqh studies and adopting the models that have been applied by neighboring countries and other Muslim countries.